(untitled) (Bangladesh Agronomy Journal, 2015)
An experiment was conducted at the Agronomy Field of Sher-e-Bangla Agricultural University, Dhaka-1207 during the period from November 2011 to March 2012 to evaluate the performance of prilled urea and urea super granules (USG) on the growth and yield of wheat varieties. The experiment comprised of four wheat varieties viz., BARI Gom 21, BARI Gom 24, BARI Gom 25 and BARI Gom 26, and five nitrogen (N) levels viz., control (no Nitrogen), 84 kg ha-1 N from USG, and 30, 50 and 70 kg N ha-1 from prilled urea i.e., 67, 112 and 155 kg urea ha-1. The experiment was laid out in a split-plot design with three replications where wheat varieties were placed in the main plot and nitrogenous fertilizers in sub-plots. Experimental results indicated that different varieties had the significant effect on plant height, number of tillers and dry weight plant-1, and number of grains spike-1, grain and straw yield, and harvest index. The variety BARI Gom 24 produced the highest grain yield (2.49 t ha-1) that mainly attributed by the maximum number of spikes plant-1, number of grains spike-1 and 1000-grain weight. Among the different nitrogenous fertilizers 84 kg N ha-1 from USG (1.8 g) gave the highest grain yield (2.69 t ha-1) due to the maximum number of spikes plant-1, maximum number of grains spike-1 and 1000-grain weight. The variety BARI Gom 24 produced the highest grain yield (2.80 t ha-1) with 80 kg N ha-1 from USG application. Bangladesh Agron. J. 2015, 18(1): 37-48